Commodity Dependence, Product Diversification, and the Implementation of the Biat Action Plan in West Africa, 2012–2022 - Ezenwegbu, Jane; Alumona, Ikenna Mike (Journal of Contemporary International Relations and Diplomacy, 2026)
West African economies exhibit a pronounced reliance on primary commodities, a structural characteristic that has historically impeded industrialization, trade competitiveness, and regional integration. This study critically examines the relationship between commodity dependence, product diversification, and the implementation of the Boosting Intra-African Trade (BIAT) Action Plan in West Africa over the period from 2012 to 2022. Drawing upon structural transformation theory and trade complementarity theory, the research investigates how limited diversification constrains the capacity of West African nations to fully capitalize on BIAT, while also exploring the potential of diversification as a catalyst for enhanced intra-regional trade. Employing a mixed-methods approach, the study integrates quantitative indicators—including export diversification indices, trade concentration ratios, and intra-regional trade shares—sourced from the UNCTAD and ECOWAS databases. This quantitative analysis is complemented by qualitative examinations of policy documents and expert insights. The findings suggest that persistent commodity dependence has significantly restricted the outcomes of BIAT. Conversely, while diversification efforts have been uneven across member states, they have positively contributed to trade complementarity and regional integration. This study highlights the dual challenge of reducing commodity dependence and fostering diversification as essential preconditions for the successful implementation of BIAT in West Africa. Furthermore, the paper contributes to the existing literature on African trade policy by linking structural economic transformation with the execution of continental integration frameworks, offering policy recommendations aimed at advancing sustainable regional trade.